PEMBENTUKAN DESA SADAR LINGKUNGAN MELALUI SOSIALISASI REGULASI PENGELOLAAN SAMPAH PLASTIK DAN PENGUATAN PERAN RT/RW DI DESA TUGU JAYA, KECAMATAN CIGOMBONG, KABUPATEN BOGOR, JAWA BARAT - Judge, Zulfikar; Yustika, Luthy; Thaher, Irmanjaya; Nurhayani, Nurhayani; Hikmawati, Elok; Siswanto, Ade Hari; Widiatno, Men Wih; Darman, Melani; Citra, Lanna Fadilla; Bertha, Anna; Widyawati, Sri; Widarto, Joko; Idris, Irdanuraprida (Jurnal Pengabdian Masyarakat AbdiMas, 2026)
AbstractPlastic waste has become one of the most serious environmental problems in Indonesia, particularly in rural areas that face limitations in waste management systems. Uncontrolled plastic waste management has caused adverse impacts on the environment, public health, and ecosystem sustainability. Low levels of public awareness and legal understanding of environmental regulations further exacerbate this condition. Therefore, strengthening community participation and local governance structures has become an urgent necessity. This Community Service Program (PkM) was conducted by lecturers of the Faculty of Law, Universitas Esa Unggul, in Tugu Jaya Village, Cigombong District, Bogor Regency, West Java, on 6–7 December 2025. The program aimed to establish an Environmentally Aware Village through the socialization of plastic waste management regulations and the strengthening of the role of neighborhood and community associations (RT/RW) as the frontline actors in environmental management. The methods employed included lectures and regulatory socialization, discussions and question-and-answer sessions, as well as educational games and the distribution of incentives, with reference to Law Number 18 of 2008 on Waste Management, Government Regulation Number 81 of 2012, and Law Number 32 of 2009 on Environmental Protection and Management. The results of the program indicate an increase in public legal awareness regarding rights and obligations in plastic waste management. The strengthening of the role of RT/RW proved effective in encouraging collective community participation and compliance with environmental regulations. Accordingly, community-based legal education serves as a strategic instrument in realizing sustainable environmental governance at the village level. Keywords: plastic waste, environmental law, community service, RT/RW, sustainable village. ABSTRAKSampah plastik telah menjadi salah satu persoalan lingkungan paling serius di Indonesia, khususnya di wilayah pedesaan yang memiliki keterbatasan sistem pengelolaan sampah. Pengelolaan sampah plastik yang tidak terkendali menimbulkan dampak negatif terhadap lingkungan hidup, kesehatan masyarakat, dan keberlanjutan ekosistem. Rendahnya kesadaran dan pemahaman hukum masyarakat terhadap regulasi lingkungan memperburuk kondisi tersebut. Oleh karena itu, penguatan peran masyarakat dan struktur pemerintahan lokal menjadi kebutuhan mendesak. Kegiatan Pengabdian kepada Masyarakat (PkM) ini dilaksanakan oleh Dosen Fakultas Hukum Universitas Esa Unggul di Desa Tugu Jaya, Kecamatan Cigombong, Kabupaten Bogor, Jawa Barat, pada tanggal 6–7 Desember 2025. Tujuan kegiatan adalah membentuk Desa Sadar Lingkungan melalui sosialisasi regulasi pengelolaan sampah plastik dan penguatan peran RT/RW sebagai garda terdepan pengelolaan lingkungan. Metode yang digunakan meliputi paparan berikut sosialisasi, diskusi dan tanya jawab serta permainan edukatif dan pemberian hadiah yang mengacu pada Undang-Undang Nomor 18 Tahun 2008 tentang Pengelolaan Sampah, Peraturan Pemerintah Nomor 81 Tahun 2012, dan Undang-Undang Nomor 32 Tahun 2009 tentang Perlindungan dan Pengelolaan Lingkungan Hidup. Hasil kegiatan menunjukkan adanya peningkatan kesadaran hukum masyarakat terkait hak dan kewajiban dalam pengelolaan sampah plastik. Penguatan peran RT/RW terbukti efektif dalam mendorong partisipasi kolektif masyarakat dan kepatuhan terhadap regulasi lingkungan. Dengan demikian, pendidikan hukum berbasis komunitas menjadi instrumen strategis dalam mewujudkan tata kelola lingkungan yang berkelanjutan di tingkat desa. Kata kunci: sampah plastik, hukum lingkungan, pengabdian masyarakat, RT/RW, desa berkelanjutan.